Characteristics of sulfated glycosaminoglycans in the cartilage tissue of skate and sturgeon - A. I. Chepkasova; T. N. Slutskaya; E. P. Karaulova (Известия ТИНРО)
Sulfated glycosaminoglycans (GAGs) or chondroitin sulfates were obtained from the cartilage tissue of skate (indefinite species) and sturgeon (kaluga) under the processes of hydrothermal treatment of raw materials at 50 оC, then hydrolysis with proteolytic enzyme in 4 hours under temperature 45 оC (hydromodulus 1 : 1), then sequential precipitation of GAGs in 2–3 volumes of 96о  ethyl alcohol and salting out with 2 % sodium chloride solution. The content of hexosamines and sulfated GAGs was determined in the extracted samples. GAGs of both skate and sturgeon have a high content of sulfated forms, comparable to commercial preparations, that opens up prospects for development of technology for production of monocomponent biologically active additives of chondroprotective action from the wastes of skates and sturgeons processing.